The Effect of Acupuncture along with Conventional Therapies on the Treatment of Allergic Rhinitis: A Clinical Trial - Sayed Mostafa Hashemi; Farhang Mokhtarinejad; Seyed Mojtaba Abtahi Forooshani; Mehran Rezvani Habibabadi (Advanced Biomedical Research)
Background: Acupuncture is one of the most important components of modern complementary medicine. Given its mechanism of action and efficacy, researchers have been recently attracted to address its efficacy in the treatment of allergic rhinitis (AR). Therefore, the present study aimed at evaluating the effect of acupuncture along with conventional therapies on the treatment of AR. Materials and Methods: The present randomized, clinical trial was performed on 51 patients with AR. All patients underwent standard AR treatment under the supervision of a specialist physician. Twenty-four patients were treated with acupuncture and 27 patients were considered as the control group. The improvement degree of AR symptoms was evaluated and recorded at baseline, 2 weeks, and 6 weeks after the treatment. Results: The results of this study revealed that a decrease in the runny nose score with a mean of 4.59 ± 3.04 and a decrease in the sneezing score with a mean of 5.30 ± 2.92 were significantly more than those of the control group with a means of 2.85 ± 1.56 and 2.78 ± 1.28, respectively (P value < 0.05). In addition, the frequency of nasal congestion, nasal itching, and tearing was significantly lower in the acupuncture group as compared with the control group (P value < 0.05). Conclusion: According to the results of the present study, although conventional AR treatments can be effective in reducing the symptoms of this disease, the use of acupuncture along with conventional AR treatments has been able to play an effective role in improving and reducing the severity of AR symptoms.